Wearable Supercapacitors Printed on Garments. (15th January 2018) - Lee, Seong‐Sun; Choi, Keun‐Ho; Kim, Se‐Hee; Lee, Sang‐Young
Abstract: Electronic garments have garnered considerable attention as a core technology for the upcoming wearable electronics era. To enable ubiquitous operation of electronic garments, they must be monolithically integrated with rechargeable power sources. Here, inspired by printing‐assisted aesthetic clothing designs, a new class of wearable supercapacitors (SCs) is demonstrated that can be directly printed on T‐shirts, which look like letters (or symbols) commonly printed on T‐shirts. The printed SCs consist of activated carbon/multiwalled carbon nanotube/ionic liquid‐based electrodes and ionic liquid/thiol‐ene polymer network skeleton/SiO2 nanoparticle‐based gel electrolytes. The rheological properties of the electrode/electrolyte pastes are fine‐tuned by varying the colloidal network structure, which affects the printing processability and formation of the nanoscale ion/electron conduction channels. To ensure the seamless unitization and design versatility of the printed SCs, the T‐shirt is sewn with electroconductive stainless steel (SS) threads prior to the printing process. Onto the SS threads acting as shape‐directing current collectors, the electrode/electrolyte pastes are sequentially stencil‐printed and sealed with water‐proof packaging films. The printed SCs exhibit exceptional form factors, flexibility, and thermal stability. Notably, the SC‐printed T‐shirts maintain their electrochemical activity upon exposure to laundering, wringing, ironing, and folding, demonstrating their potential and practical applicability as a promising electronic garment technology. Abstract : Wearable supercapacitors (SCs) printed on T‐shirts are demonstrated as a new class of aesthetically unitized power source with exceptional design versatility and flexibility. The SC‐printed T‐shirts show great potential as an effective/scalable electronic garment platform for the forthcoming wearable electronics era.